Family Empowerment Through Clean and Healthy Living Behavior Program - K, Ernawati S (Universitas Negeri Makassar, 2024)
The research objective of this article is to describe and analyze the impact of empowerment on families from clean and healthy living behavior programs through programs launched by PKK mothers in Tamalanrea Village, Makassar. Article research uses a qualitative research approach and a type of research, namely descriptive-qualitative. Data collection using observation, interview and documentation techniques. The technique of withdrawing informants is carried out deliberately using several criteria. Checking the validity of data is using source trigulation. Data analysis techniques use descriptive-qualitative analysis through the stages of data reduction, data presentation, and conclusions. The results of research from this article found that empowerment of families through clean and healthy living behavior programs (PHBS) carried out by PKK mothers has had a positive impact on family members, and society in general. The empowerment of family members and the community is seen through the application of clean and healthy living behaviors, such as washing hands using soap and clean water, disposing of garbage in its place, draining water troughs and not smoking in the house. However, there are still some community members who lack awareness in understanding healthy lifestyles in general associated with PHBS. This will certainly cause disease outbreaks in the community and result in a decrease in their productivity. Then it can have a negative impact on economic performance and community development.